Dolina Baruna pod Makalujem (8465 m) - Kunaver, Jurij (Geografski obzornik, 2025)
This article is a continuation of the previous one, from the first issue of this year’s Geografski obzornik. The 1972 expedition and a smaller one in 2014 produced abundant material. We address climate-driven changes in the Barun Valley, typical of high-mountain areas: glacier retreat, the expansion and increasing number of glacial lakes that may threaten lower regions. Earthquakes, landslides and rockfalls can trigger sudden floods. We also summarize findings from the monograph published for the 50th anniversary of the 4th JAHO, focusing on geology, flora, fauna and altitudinal zones of the wider area.
Keywords: Eastern Himalayas; flora and fauna; geographical name; geologija; geology; geomorfologija; glacial relief; ledeniški relief; Makalu Barun National Park; Narodni park Makalu Barun; rastlinstvo; Vzhodna Himalaja; zemljepisna imena; živalstvo